Standardisation and language criticism in German - Felder, Ekkehard; Jacob, Katharina (Handbuch europäische Sprachkritik online, 2018)
Standardisation is mainly discussed in relation to language history, language variation and sociolinguistics. Investigations of the role of standardisation in German language criticism are as yet a desideratum. However, individual aspects of standardisation are sometimes consulted for the explanation or evaluation of language criticism in German. This article describes forms of language reflexion and language criticism as regulatory aspects for orienting orality and literacy to norms. First, authorities and institutions guiding the process of standardisation are discussed (e. g. church, nobility, bourgeoisie, scholars, linguistic societies, publications, or rhetorical and stylistic principles). Second, domains that were to be standardised are mentioned (e. g. lexis, syntax). In addition to the historical perspective, this article looks at current issues about standardisation in correlation with language criticism.
Gesehen am 04.05.2023